The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1891/0886-6708.vv-d-16-00118
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Victimization and Cognitive Function in a Mixed-Sex Epidemiological Sample of Urban Adults

Abstract: Intimate partner violence (IPV) victimization is associated with a wide range of mental and physical health problems, but little is known about the effect of IPV on cognitive decline. Previous research suggests an association between IPV victimization and cognitive dysfunction, but the few studies that have examined this phenomenon were cross-sectional in design and focused only on female victims of IPV. The current study examined cognitive function over time among a diverse population of both male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…There is an association between posttraumatic symptoms and low cognitive performance in women exposed to violence (13,14). Therefore, one of the objectives of this study was to identify the existence of a relationship between clinical symptomatology and low cognitive performance, in addition to determining whether EMDR therapy and NET generated positive effects in the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an association between posttraumatic symptoms and low cognitive performance in women exposed to violence (13,14). Therefore, one of the objectives of this study was to identify the existence of a relationship between clinical symptomatology and low cognitive performance, in addition to determining whether EMDR therapy and NET generated positive effects in the participants.…”
Section: Discussionmentioning
confidence: 99%
“…A latent association has been identified between clinical symptoms and cognitive functioning in this group of women (12). In this sense, women who report anxiety, depression, posttraumatic stress, or exposure to sexual violence tend to show low performance in neuropsychological evaluations, especially in attentional, visuospatial and executive tasks (13,14). Added to this is the evidence that sociodemographic factors are related to the adverse effects of violence on the physical and mental health of female victims (15) as well as on their quality of life (16).…”
Section: Introductionmentioning
confidence: 97%
“…Studies found a significant positive correlation 10. 3389/fnbeh.2022.943081 between IPV history and long-term decay in cognitive performances (Williams et al, 2017) likely due to the strong involvement of cognitive functions in emotional processing. It has also been argued that this cognitive-emotional impairment might also preclude the IPV survivors' response to treatments, thus exacerbating the psychopathological sequelae of IPV.…”
Section: Cognitive and Emotional Alterations In Ipv Survivorsmentioning
confidence: 99%
“…The physical and mental health consequences have often been reported in the scientific literature but focus primarily on victims (Lagdon et al, 2014;Pengpid & Peltzer, 2020;Próspero, 2007;Williams, Murphy, Dore, Evans, & Zonderman, 2017). Fewer studies have focused on the consequences for the perpetrator's health, including mental health, or the influence of psychological IPV (Heise et al, 2019).…”
Section: Introductionmentioning
confidence: 99%